Kualitas Pelayanan Pemerintah Daerah - Ismail Bagus Fauzi; Hanny Purnamasari; Kariena Febriantin (Peneliti.net, 2022)
This study aims to determine and examine the quality of local government services (Descriptive Study of Public Service Malls at Lotte Mart Building, North Cikarang, Bekasi Regency). The theory used in this study is the service quality of Zeithaml in (2017, p. 11) where there are five dimensions which include physical evidence (tangibles), Reliability (Relliability), Responsiveness (Responsiviness), Assurance (Assurance) and Attention (Empathy). . The method used is descriptive qualitative research method, data collection technique is triangulation which includes interviews, observation and study of documentation of data then analyzed using the concept of analysis of reduction, presentation and conclusions drawn. The results of the research and discussion show that the quality of public services at the Public Service Mall (MPP) Bekasi Regency is not optimal because the building used is not able to accommodate many community visits, the community does not receive calls to fulfill public service rights, policies that have not led to the hospitality of persons with disabilities. and the use of the internet in the registration of public services at MPP is considered not yet able to reach all elements of society, especially the people of Bekasi Regency who are stuttering about technology